The DairyVIP Program to Evaluate the Consequences of Changes in Herd Management and Prices on Dairy Farms - Albert De Vries (EDIS, 2006)
AN177, a 12-page illustrated fact sheet by Albert De Vries, explains some of the methods and describes the input and output sheets of DairyVIP, a computer program for dairy herd management. Published by the UF Animal Sciences Department, September 2006.